2005
DOI: 10.1111/j.1744-7909.2005.00061.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation and Clonal Diversity of the Two Divergent Types of Clonal Populations of Leymus chinensis Tzvel on the Song Liao Steppe in the West of Northeastern China

Abstract: Abstract:The genetic variation and clonal diversity of two divergent types (grey-green and yellow-green) of clonal populations of Leymus chinensis Tzvel at 14 loci were compared. Total gene diversity (H T ) and the coefficient of genetic differentiation (G ST ) were all higher for the yellow-green type (H T = 0.270; G ST = 0.186) than for the grey-green type (H T = 0.250; G ST = 0.157) of L. chinensis. Rare alleles usually occurred as heterozygotes rather than homozygotes and significant deviations from Hardy-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…In this study it was also found that the grey-green accessions had more variation than the yellow-green accessions, as indicated by a wider scattering of the grey-green group in the PCO analysis ( Figure 2). This was supported by the results of Cui et al (2000) but not those of Wang et al (2005). This discrepancy was most likely related to limited number of loci, with nineteen putative loci in ten enzyme systems in the work of Wang et al (2005).…”
Section: Discussionmentioning
confidence: 53%
See 4 more Smart Citations
“…In this study it was also found that the grey-green accessions had more variation than the yellow-green accessions, as indicated by a wider scattering of the grey-green group in the PCO analysis ( Figure 2). This was supported by the results of Cui et al (2000) but not those of Wang et al (2005). This discrepancy was most likely related to limited number of loci, with nineteen putative loci in ten enzyme systems in the work of Wang et al (2005).…”
Section: Discussionmentioning
confidence: 53%
“…Cui et al. (2000) and Wang et al. (2005), however, demonstrated that there was a stable genetic difference between the two types and indicated that the result of Zhang et al.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations